2008
DOI: 10.1089/neu.2007.0409
|View full text |Cite
|
Sign up to set email alerts
|

Uridine Protects Cortical Neurons from Glucose Deprivation-Induced Death: Possible Role of Uridine Phosphorylase

Abstract: We previously reported that uridine blocked glucose deprivation-induced death of immunostimulated astrocytes by preserving ATP levels. Uridine phosphorylase (UPase), an enzyme catalyzing the reversible phosphorylation of uridine, was involved in this effect. Here, we tried to expand our previous findings by investigating the uridine effect on the brain and neurons using in vivo and in vitro ischemic injury models. Orally administrated uridine (50-200 mg/kg) reduced middle cerebral artery occlusion (1.5 h)/repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
24
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 38 publications
7
24
0
2
Order By: Relevance
“…Neurons, especially those residing in the hippocampus and cortex, are highly sensitive to GD (Auer et al, 1984; Monyer and Choi, 1988; Monyer et al, 1989; Goldberg and Choi, 1993), whereas astrocytes have been demonstrated to be more resistant (Monyer and Choi, 1988; Monyer et al, 1989; Goldberg and Choi, 1993; Lyons and Kettenmann, 1998) (Figure 1). This is in accordance with the findings that rapid ATP depletion occurs exclusively in neurons following GD in vitro (Choi et al, 2008) and that astrocytes contain glycogen stores (Cataldo and Broadwell, 1986; Swanson et al, 1990) that can be metabolized to meet their own metabolic needs (Swanson et al, 1990; Erecinska and Silver, 1994; Dienel and Cruz, 2006; Walls et al, 2009). Additionally, the ability to convert glutamate to pyruvate provides another possible mechanism whereby the tricarboxylic acid cycle in astrocytes can be maintained when levels of glucose are low (Bakken et al, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…Neurons, especially those residing in the hippocampus and cortex, are highly sensitive to GD (Auer et al, 1984; Monyer and Choi, 1988; Monyer et al, 1989; Goldberg and Choi, 1993), whereas astrocytes have been demonstrated to be more resistant (Monyer and Choi, 1988; Monyer et al, 1989; Goldberg and Choi, 1993; Lyons and Kettenmann, 1998) (Figure 1). This is in accordance with the findings that rapid ATP depletion occurs exclusively in neurons following GD in vitro (Choi et al, 2008) and that astrocytes contain glycogen stores (Cataldo and Broadwell, 1986; Swanson et al, 1990) that can be metabolized to meet their own metabolic needs (Swanson et al, 1990; Erecinska and Silver, 1994; Dienel and Cruz, 2006; Walls et al, 2009). Additionally, the ability to convert glutamate to pyruvate provides another possible mechanism whereby the tricarboxylic acid cycle in astrocytes can be maintained when levels of glucose are low (Bakken et al, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…It could also be speculated that uridine's cerebroprotection involves hypothermia, as has been demonstrated previously [21]. It is also possible that the cerebroprotective effects of uridine observed in the present study might have arisen from the action of uridine phosphorylase, which provided protection from glucose deprivation-induced death of immunostimulated astrocytes [10] and cortical neurons [11] and have involved both neurons and astrocytes. However, precise mechanism(s) of uridine action in this model needs further investigation.…”
Section: Discussionsupporting
confidence: 77%
“…Chronic supplementation with uridine-5-monophosphate (UMP) increases levels of phospholipids, synaptic proteins and leads to synaptogenesis in adult [24,34] and newborn rodents [6]. Evidence that uridine might confer benefit under degenerative conditions has been provided by in vitro glucose deprivation studies [10,11] as well as in vivo rat model of Parkinson's [7].…”
Section: Discussionmentioning
confidence: 99%
“…Given also that a crucial metabolic end product of uridine catabolism is β-alanine, a precursor to fatty acid synthesis, it may be that disruption of the supply of uridine metabolites may mitigate cellular damage upon exposure to oxidative stress by moderating concurrent lipid biosynthesis. Alternately, tissue uridine concentrations can be elevated by blocking UPP activity (Chu et al, 1984) and uridine has been shown to have cyto-protective properties (Choi et al, 2006, 2008). Thus raising endogenous uridine levels in reaction to a redox imbalance may be a general cellular defensive response and possibly not limited to liver tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond cancer, elevating uridine concentrations in combination with docosahexaenoic acid administration is being explored as a potential treatment for both Alzheimer’s disease (Holguin et al, 2008) and Parkinson’s disease (Cansev et al, 2008). Uridine has also been found to be cyto-protective in astrocytes exposed to metabolic stresses, such as ischemia (Choi et al, 2006, 2008). Thus, development of selective inhibitors, capable of discriminating between the two human homologues of UPP so as to raise endogenous uridine levels in a specific subset of tissues, may yield novel methods for the treatment of an array of diseases.…”
Section: Discussionmentioning
confidence: 99%